Assessment of the performance persistence of Employee Capital Plans - Banaś, Dawid (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Estimating the future return rates is virtually impossible. However, it is possible to verify whether financial institutions that invest entrusted funds are able to maintain high rates of return for along time. This phenomenon is referred to as performance persistence, and has become the object of interest of the author of this article in relation to Employee Capital Plans (ECP). A research hypothesis was adopted that performance persistence in ECP does occur. It was verified using contingency tables that were created for defined date funds that operate in ECP, using monthly rates of return and the Sharpe index. The results obtained by the author allowed concluding that the performance persistence of rates of return in the case of ECP occurs for amaximum of half of the research period.
Keywords: long-term saving; retirement security; Employee Capital Plans; performance persistence; repeatability of results; pension funds